2014
DOI: 10.1093/hmg/ddu571
|View full text |Cite
|
Sign up to set email alerts
|

Loss of the thyroid hormone-binding protein Crym renders striatal neurons more vulnerable to mutant huntingtin in Huntington's disease

Abstract: The mechanisms underlying preferential atrophy of the striatum in Huntington's disease (HD) are unknown. One hypothesis is that a set of gene products preferentially expressed in the striatum could determine the particular vulnerability of this brain region to mutant huntingtin (mHtt). Here, we studied the striatal protein µ-crystallin (Crym). Crym is the NADPH-dependent p38 cytosolic T3-binding protein (p38CTBP), a key regulator of thyroid hormone (TH) T3 (3,5,3′-triiodo-l-thyronine) transportation. It has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 56 publications
3
26
0
Order By: Relevance
“…To our knowledge, the discovery that μ-crystallin is specific for striatal astrocytes provides the first molecular marker that defines a region-specific astrocyte population. Moreover, striatal astrocytes are known to be altered in Huntington’s disease (HD) (Khakh et al, 2017) and μ-crystallin levels decrease in humans and mouse models of HD (Francelle et al, 2015). Interestingly, six of the top 40 striatal enriched astrocyte genes are histones, which is consistent with the GSEA results that chromosome structure-related gene sets were striatal enriched.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, the discovery that μ-crystallin is specific for striatal astrocytes provides the first molecular marker that defines a region-specific astrocyte population. Moreover, striatal astrocytes are known to be altered in Huntington’s disease (HD) (Khakh et al, 2017) and μ-crystallin levels decrease in humans and mouse models of HD (Francelle et al, 2015). Interestingly, six of the top 40 striatal enriched astrocyte genes are histones, which is consistent with the GSEA results that chromosome structure-related gene sets were striatal enriched.…”
Section: Discussionmentioning
confidence: 99%
“…We identified 2 key drivers that met all 5 criteria (Figure 5B-I): crystalin mu (Crym) and prostaglandin D2 synthase (Ptgds). Crym is a thyroid hormonebinding protein (Hallen et al, 2011;Vie et al, 1997), a non-canonical transcriptional regulator (Ohkubo et al, 2019), and is neuroprotective in striatum (Francelle et al, 2015), while Ptgds is a pro-inflammatory enzyme which catalyzes the production of prostaglandin D (Urade and Hayaishi, 2011). Since we hypothesized that transcriptional changes within meA drive sex-specific changes in behavior, we chose to focus on Crym ( Figure 5J-M).…”
Section: Co-expression Analysis Reveals That Feminization and Masculimentioning
confidence: 99%
“…Previous studies have reported downregulation of CRYM mRNA in Huntington's disease models and patients and CRYM plays a neuroprotective role in the striatum of Huntington's disease model mice . Huntington's disease is a neurodegenerative disease characterized by loss of neurons in the caudate nucleus resulting in involuntary movements and cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%